THE RISE AND FALL OF THE FISHERY FOR SILVER SCABBARDFISH, LEPIDOPUS CAUDATUS EUPHRASEN, 1788 (ACTINOPTERYGII; TRICHIURIDAE) IN THE LIGURIAN AND NORTHERN TYRRHENIAN SEA (NW MEDITERRANEAN) - Ligas, Alessandro; Musumeci, Claudia; Rossetti, Ilaria; Sartini, Marina; Sartor, Paolo; Sbrana, Mario; Viva, Claudio; Pretti, Carlo (Biologia Marina Mediterranea, 2024)
In the early 2000s in the Ligurian and northern Tyrrhenian Sea (NW Mediterranean), new fisheries targeting Lepidopus caudatus Euphrasen, 1788 (Actinopterygii; Trichiuridae) were developed. These fisheries used ad hoc bottom trawl nets with higher vertical opening, gillnets and longlines. Development of these fisheries was not regulated by any specific management measure and, due to the progressive reduction of catches, the target fisheries stopped. A stock assessment using data-limited tools (namely AMSY and CMSY) was performed confirming the overexploitation of silver scabbardfish.